PROTECTION OF WOMEN'S RIGHTS IN THE PRACTICE OF REMARRIAGE CONTRACTS DUE TO OUT-OF-WEDLOCK PREGNANCY: A STUDY IN TANJUNG PURA DISTRICT, LANGKAT REGENCY - Laila Suhada; Sukiati Sukiati; Fatimah Fatimah (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
This study aims to analyze the protection of women's rights in the practice of remarriage contracts (akad nikah ulang) conducted after the birth of a child conceived out of wedlock in Tanjung Pura District, Langkat Regency. Normatively, Article 53 paragraph (3) of the Indonesian Compilation of Islamic Law (KHI) explicitly stipulates that a marriage performed while a woman is pregnant does not require a remarriage contract after the child is born. However, in social practice, this phenomenon persists due to the belief that the initial contract merely legitimizes the unborn child, whereas the second perfects the marital bond. Employing an empirical juridical method with a socio-legal approach, primary data were collected through interviews with religious leaders, KUA registrars, community figures, and practicing couples. Data were qualitatively analyzed using Islamic law, Indonesian positive law, and women's legal protection theories. The findings reveal that religious caution (iḥtiyāṭ), social pressure, stigma, and the pursuit of moral legitimacy primarily drive this practice. From the Shafi'i School perspective, remarriage is not obligatory if the initial contract fulfills all essential pillars and requirements. Similarly, Indonesian positive law provides no juridical basis for such practices. Consequently, this practice significantly impacts women's rights, reinforcing social stigma, imposing psychological burdens, undermining legal certainty regarding women's marital status, and reproducing gender inequalities within society. Furthermore, the study highlights the urgent need for structural intervention by state apparatuses and religious institutions to mitigate customary practices that systematically disadvantage women under the guise of religious perfection.